MENINGKATKAN KESEJAHTERAAN MASYARAKAT MELALUI PENGELOLAAN SAMPAH BERDASARKAN UU NO. 18 TAHUN 2008 - Qodriyatun, Sri Nurhayati (Jurnal Aspirasi, 2014)
People have always produced waste and it is become a problem if not managed properly. The Act No.18 of 2008 on Waste Management has shift the paradigm of waste management to a resource that has economic value useful for human life as to improve the welfare of society. This research used a qualitative approach with descriptive method, which aims at describing waste management based on the Act No. 18 of 2008 so as to improve the welfare of society. The results showed that waste management as mandated by the Act No. 18 of 2008, has brought many benefits for the improvement of the well-being of the community in the city of Malang. With a strong commitment, local government found innovative ways in utilizing waste in the city.